Efektivitas Manajemen Pendidikan Berbasis Islam terhadap Karakter Lulusan di SMA Al-Hidayah Medan - Siregar, Rizka Zusanti; Siregar, Astri Novia (UMSU, 2024)
This research aims : 1. to find out of planning for Islamic-based education at Al-Hidayah High School Medan, 2. to find out the organization of Islamic-based education at Al-Hidayah High School Medan, 3. to know the implemen tation of Islamic-based education at Al-Hidayah High School Medan, 4. to find out the character of graduates with education-based education. Islam at Al-Hidayah High School Medan, 5. Islamic-based educational management is effective in producing the character of graduates at Al-Hidayah High School Medan. This research uses qualitative descriptive methods. The sub ject is the principal, teacher at Al-Hidayah High School in Medan. The data sources used in this research are primary data and secondary data which are needed to find out how Islamic-based education is implemented at SMA Al-Hidayah Medan. Data was collected through interviews, observation and documentation. The research results show that Islamic-based education has been successfully implemented optimally according to the direction of the school principal and also the support of the teachers. The dominant factor that influences the character of Al-Hidayah Medan High School graduates is religious activities which are able to shape students' characters into characters with noble morals. AlHidayah Medan High School is now a driving school which is a role model for driving schools in the surrounding environment. Student activity in extra-curricular activities tahfizh, tahsin, muhadharah (speech in three languages) was carried out optimally. The implementation of Islamic-based education will improve the character of Al-Hidayah Medan High School graduates into better individuals, responsible and of noble character. The school which was previously known as ALTEK (Al-Hidayah Teksas) has now changed to ALBAT (Al-Hidayah Hebat).